Country report. Lebanon - Economist Intelligence Unit (London Economist Intelligence Unit, 2005)
Each Country Report contains in-depth and ongoing analysis and forecasts of political, policy and economic conditions to help you understand what is happening now and to gain a picture of how Lebanon will look in the future
The library has one issue only (Oct 2005)
Keywords: Economic conditions; ECONOMIC POLICY; ECONOMIC CONDITIONS; POLITICAL CONDITIONS; LEBANON; PERIODICALS